AKREDITASI MADRASAH ALIYAH (MA) DALAM KEBIJAKAN PENDIDIKAN NASIONAL - Ikhwan, Afif (e-Journal STAI Muhammadiyah Tulungagung, 2014)
Accreditation is a small boomerang for themanager in improving the quality of education ifthe quality of the legal juridical madrasah be aninternal conflict in the external even hit the targetquantity instead of quality and customersatisfaction neglect veiled on mutualism occurs inthe transaction value of education in madrasah, nottoo much to said that the accreditation madrasah /school can be angled in marketable education thatleads to the money, who gets the profit is thedemand in the market of education, and the